Inversión económica vs pérdidas de agua no contabilizada en planes maestros de agua potable en Ecuador - Villa Guilcapi, Hugo Francisco (2024)
In Ecuador, a noteworthy percentage of the losses in the distribution systems of potable water is triggered by leaks which affect both municipalities and the companies responsible of the management of this service. Despite substantial investments made in the development of Master Plans for drinking water in the studied cantons (Colta, Chimbo, Alausí, Guano, Tisaleo), the unaccounted-for water index remains high, exceeding the national average. In this regard, the study aimed to analyze the relationship between the investment attributed to the mentioned Plans and the water losses in these cantons. To assess the correlation between these two variables, the study was carried out under the principles of the quantitative approach that includes stages of data collection, processing, and analysis. The Pearson correlation coefficient (R) and the coefficient of determination (R²) were used to measure the strength and direction of the statistical association between the variables. Results evidence that there is no significant relationship between the funding consigned to the Master Plans and the water losses in the study contexts. Furthermore, a significant correlation has been determined between the rate per cubic meter of potable water and the Unaccounted-For Water Index (IANC). Consequently, results suggest that as the potable water tariff increases, a reduction in the IANC is observed.